Anti-CCP Antibodies: an Emerging Marker for the Early Diagnosis of Rheumatoid Arthritis - K , Sarah; A, Nadeem (IIUM Medical Journal Malaysia, 2010)
Rheumatoid arthritis (RA) is a systemic disease affecting mainly joints. Since rheumatoid arthritis is a common and a world wide problem therefore accurate diagnosis of this disease is essential. In the past rheumatoid factor was considered as the only marker for diagnosing this disease; however rheumatoid factor is present in many other disorders and even in up to 15% of healthy population. For the detection of rheumatoid arthritis, over the years many auto antibodies have been reported such as anti perinuclear factor (APF) and anti keratin antibodies (AKA) but they were not specific and due to the tedious procedure used for their laboratory diagnosis, they could not become popular for the diagnosis of this disease. Recently anti-CCP antibodies have been reported and they are becoming popular due to their high sensitivity and specificity. It is hoped that in a couple of years time anti-CCP antibodies could be included in the ACR criteria for diagnosing RA.